Stablecoins as a New Monetary Layer: Market Structure, Reserve Design, and the Competition with Tokenized Deposits - Mirdala, Rajmund (Theoretical and Practical Research in Economic Fields; Vol 17 No 2 (2026): TPREF Volume XVII Issue 2(38) June 2026, 2026)
Stablecoins have evolved from liquidity tools for crypto trading into a form of tokenized private money with implications for payments, cross-border transfers, short-term funding markets, and the architecture of money itself. The literature on stablecoins has expanded rapidly but remains fragmented across stability, reserve design, banking, payments, and regulation. This paper synthesizes that literature into a single integrative argument: stablecoins should be analyzed as a distinct monetary layer within tokenized finance, evaluated against the BIS framework of singleness, elasticity, and integrity, and compared with tokenized deposits as their most relevant institutional alternative. Drawing on descriptive market evidence and a structured institutional comparison, the paper shows that the stablecoin sector is highly concentrated and overwhelmingly dollar-based; that reserve-backed stablecoins transmit on-chain demand into safe-asset markets and bank funding through three identifiable channels – Treasury and short-term funding, bank funding, and the global safe-asset channel; and that stablecoins and tokenized deposits embody distinct institutional models of programmable money with different welfare and stability implications. The paper concludes that, under recent regulatory developments including MiCA in the European Union and the GENIUS Act in the United States, the most coherent monetary architecture is one in which central bank money remains the ultimate settlement anchor, tokenized deposits extend regulated bank money into programmable environments, and stablecoins operate as specialized private instruments under strong constraints on reserves and redemption.